A modified lithium iron manganese phosphate positive electrode material and its preparation method and application

By designing the core-shell structure of the modified iron-manganese lithium lithium positive electrode material, the buffer layer is used to suppress manganese dissolution and increase the specific surface area, the problem of manganese dissolution in iron-manganese lithium iron-manganese lithium is solved, and the circulation performance and conductivity of the battery are significantly improved.

CN119153668BActive Publication Date: 2025-02-11湖南泓原新能源科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411639995.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

During charging and discharging of lithium iron manganese phosphate, manganese dissolution due to the ginger Taylor effect of manganese ions, seriously destroying the structure of the electrolyte and reducing the battery circulation performance.

Method used

Design a modified iron-manganese lithium lithium phosphate positive electrode material, adopting a core-shell structure, with iron-manganese lithium phosphate as the core and lithium iron phosphate as the shell, and there are two buffer layers in the middle. The first buffer layer is formed by sintering of carboxymethyl cellulose lithium , the second buffer layer is formed by sintering a mixture of lithium iron phosphate and lithium carboxymethylcellulose.

Benefits of technology

Effectively inhibit the dissolution of manganese, increase the specific surface area of ​​the material, shorten the lithium ion transmission distance, and improve the conductivity and electrochemical properties of the positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 9OWC7E2MEPB6IEN7IIPQW2FDCWP5XBKX1W18BD3M
    Figure 9OWC7E2MEPB6IEN7IIPQW2FDCWP5XBKX1W18BD3M
  • Figure S84EACL45UKDW2GOV8TREDJAFXIHSLEYKHL8KDQ6
    Figure S84EACL45UKDW2GOV8TREDJAFXIHSLEYKHL8KDQ6
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium batteries, and specifically to a modified lithium iron manganese phosphate positive electrode material, and a preparation method and application thereof. The modified lithium iron manganese phosphate positive electrode material includes a lithium iron manganese phosphate core material and a lithium iron phosphate shell coated outside the lithium iron manganese phosphate core material; the lithium iron manganese phosphate core material includes a lithium iron manganese phosphate core body, a first buffer layer coated outside the lithium iron manganese phosphate core body, and a second buffer layer coated outside the first buffer layer; the first buffer layer is mainly sintered from lithium carboxymethyl cellulose, and the second buffer layer is mainly sintered from a mixture of lithium iron phosphate and lithium carboxymethyl cellulose. The present invention designs a core-shell structure, with lithium iron manganese phosphate as the core and lithium iron phosphate as the shell, wherein the first buffer layer and the second buffer layer serve as an intermediate skeleton, which can not only effectively inhibit the dissolution of manganese, but also provide sufficient lithium ions for the positive electrode material, has excellent conductivity, first charge and discharge capacity, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically, to a modified lithium iron manganese phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] The most commonly used positive electrode materials in lithium batteries are lithium iron phosphate and ternary materials. Compared with ternary materials, lithium iron phosphate (LFP) has better safety performance and cycle stability, and its raw material sources are wide and the cost is low. However, the energy density of lithium iron phosphate is low, which makes it unable to meet the specific needs of some products.

[0003] Lithium manganese iron phosphate (LMFP) is an olivine-type phosphate positive electrode material obtained by doping manganese (Mn) on LFP. It inherits the excellent cycle performance and safety of LFP, and the high voltage characteristics of manganese make LMFP have a higher voltage platform and energy density, which can take into account both high safety and high energy density.

[0004] However, during the charge and discharge of lithium iron manganese phosphate, the Jan-Taylor effect of manganese ions will cause manganese dissolution, which seriously damages the structure of the electrolyte, thereby reducing the battery cycle performance. To this end, the existing publication number CN116873892A improves the problem of manganese dissolution in lithium iron manganese phosphate by doping elements and changing the ratio of the reaction solution, and the molar content of manganese element in the direction from the center to the surface of the prepared lithium iron manganese phosphate positive electrode material decreases in a gradient, and the molar content of iron element and aluminum element increases in a gradient. However, the above scheme has limited effect on the improvement of manganese dissolution, and further improvement is needed. Summary of the invention

[0005] In order to effectively improve the problem of manganese dissolution in lithium iron manganese phosphate, the present invention provides a modified lithium iron manganese phosphate positive electrode material and a preparation method and application thereof.

[0006] In a first aspect, the present invention provides a modified lithium iron manganese phosphate positive electrode material, comprising a lithium iron manganese phosphate core material and a lithium iron phosphate shell coated outside the lithium iron manganese phosphate core material; the lithium iron manganese phosphate core material comprises a lithium iron manganese phosphate core body, a first buffer layer coated outside the lithium iron manganese phosphate core body, and a second buffer layer coated outside the first buffer layer; the first buffer layer is mainly sintered from lithium carboxymethyl cellulose, and the second buffer layer is mainly sintered from a mixture of lithium iron phosphate and lithium carboxymethyl cellulose.

[0007] Preferably, the weight ratio of the lithium iron manganese phosphate core material to the lithium iron phosphate shell is 60-70:40-30.

[0008] Preferably, the weight ratio of the lithium iron manganese phosphate core, the first buffer layer and the second buffer layer in the lithium iron manganese phosphate core material is 56-67:2-3:1.

[0009] Preferably, the weight ratio of the lithium iron manganese phosphate core, the first buffer layer and the second buffer layer in the lithium iron manganese phosphate core material is 60:3:1.

[0010] Preferably, the weight ratio of the lithium iron phosphate to the lithium carboxymethyl cellulose is 0.3-0.6:1.

[0011] In a second aspect, the present invention provides a method for preparing a modified lithium iron manganese phosphate positive electrode material, comprising the following steps:

[0012] Primary coating: Take an appropriate amount of lithium iron manganese phosphate powder and put it into an aqueous solution of lithium carboxymethyl cellulose for uniform dispersion by ball milling, and harvest the primary coating material after drying;

[0013] Secondary coating: taking a set amount of lithium iron phosphate and lithium carboxymethyl cellulose and dispersing them in water to obtain a mixture, adding the primary coating material into the mixture and ball milling to disperse it evenly, and harvesting the secondary coating material after drying;

[0014] Sintering composite: adding a phosphorus source, an iron source and a lithium source to the secondary coating material and mixing them evenly, firstly performing a hydrothermal reaction to obtain a precursor, and then performing a sintering treatment on the precursor to obtain the modified lithium iron manganese phosphate positive electrode material.

[0015] Preferably, in the first coating step, the drying treatment condition is drying at a temperature of 100-120°C for 1-2 hours; in the second coating step, the drying treatment condition is drying at a temperature of 130-150°C for 1-2 hours.

[0016] Preferably, in the sintering and compounding step, the hydrothermal reaction is carried out at a temperature of 160-180° C. for 6-8 hours.

[0017] Preferably, in the sintering and compounding step, the sintering treatment includes pre-sintering and calcining, the pre-sintering is performed at a temperature of 300-350° C. for 2-3 hours, and the calcining is performed at a temperature of 750-800° C. for 6-8 hours.

[0018] In a third aspect, the present invention provides the use of modified lithium iron manganese phosphate positive electrode material in the preparation of a positive electrode for a lithium ion battery.

[0019] In summary, the present invention has the following beneficial effects:

[0020] 1. The present invention designs a core-shell structure with lithium iron manganese phosphate as the core and lithium iron phosphate as the shell, wherein the first buffer layer and the second buffer layer serve as the intermediate skeleton, and the main component of the first buffer layer is lithium-containing carbide, which can effectively inhibit the dissolution of manganese; the second buffer layer contains lithium iron phosphate in addition to lithium-containing carbide, but the content of lithium iron phosphate is lower than that of the lithium iron phosphate shell, thereby gradually increasing the content of lithium iron phosphate from the inside to the outside, providing sufficient lithium ions for the positive electrode material.

[0021] 2. The first buffer layer and the second buffer layer of the present invention can firmly bond the lithium iron manganese phosphate core to the lithium iron phosphate shell before sintering. Water vapor, carbon monoxide, carbon dioxide, etc. will also be generated during the sintering process, which can not only generate pores in the buffer layer itself, but also form more pores on the lithium iron phosphate shell coated on the outer layer, thereby forming a conductive network channel inside the positive electrode material, increasing the specific surface area of ​​the material to shorten the lithium ion transmission distance, and facilitating the lithium ions in the lithium iron manganese phosphate core to be able to escape and embed faster.

[0022] 3. The present invention further limits the amount of the lithium iron manganese phosphate core, the first buffer layer and the second buffer layer, the lithium iron phosphate shell, and the lithium iron phosphate and lithium carboxymethyl cellulose hydrogel. The above components will affect the performance of the positive electrode material to a certain extent, so it is necessary to select a suitable amount.

[0023] 4. The method of the present invention uses a primary coating to perform preliminary shaping first, and then uses a secondary coating to ensure the basic structure of the lithium iron manganese phosphate core, and finally sintering and composite forming in one time, which can reduce the calcination steps of preparing the lithium iron manganese phosphate core separately; in addition, the lithium iron phosphate shell in the present invention is formed by first adding raw materials and then sintering, which helps to improve the composite effect of the lithium iron phosphate shell and the second buffer layer, reduce the interface resistance, and further improve the conductivity of the positive electrode material. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0025] Raw materials and preparation examples

[0026] The raw materials of the present application are all commercially available products in the following preparation examples.

[0027] Among them, the specific surface area of ​​lithium iron manganese phosphate powder is 19.34m 2 / g, tap density is 0.98g / cm3 The particle size D50 is 0.936μm, the lithium content is 4.3%, the manganese content is 20.83%, the iron content is 13.96%, the phosphorus content is 19.01%, and the carbon content is 1.88%.

[0028] The specific surface area of ​​lithium iron phosphate powder is 10.0±1.5m 2 / g, tap density ≥0.8g / cm 3 , particle size D50 is 0.6-1.8μm, first discharge capacity ≥150mAh / g, first charge capacity ≥154mAh / g, first discharge efficiency ≥95%.

[0029] The phosphorus source may be selected from any one of diammonium phosphate, ammonium phosphate, diammonium phosphate, lithium dihydrogen phosphate or phosphoric acid, or a combination of at least two thereof.

[0030] The iron source may be selected from any one of ferrous phosphate, ferrous oxalate, ferrous sulfate or ferrous chloride, or a combination of at least two thereof.

[0031] The lithium source can be selected from any one of lithium carbonate, lithium hydroxide or lithium acetate, or a combination of at least two thereof.

[0032] Preparation example of lithium carboxymethyl cellulose:

[0033] ① Alkalization: 220g cotton pulp was shredded and put into a 5L kneader together with 800mL triethylamine aqueous solution (80%). After the feeding was completed, it was stirred at room temperature for 2h, and the air in the kneader was removed. Nitrogen was filled into the kneader and alkalized for 80min under nitrogen protection. The alkalization temperature was 30℃;

[0034] ② Etherification: Add 90 mL of etherifying agent chloroacetic acid into the kneader in batches, gradually raise the temperature to 80°C, and continue the reaction for 80 minutes to obtain carboxymethyl cellulose triethylamine ammonium salt;

[0035] ③ Purification: remove the residual triethylamine in the material through the stripping process;

[0036] ④ Lithiation: Add 180g of carboxymethyl cellulose triethylamine ammonium salt to 2kg of ethanol / water solvent (75:25) system, then add 10% LiOH aqueous solution, the mass ratio of LiOH to carboxymethyl cellulose triethylamine ammonium salt dry sample is 0.34:1. The above mixed solution is reacted at 40°C for 2h, then neutralized with glacial acetic acid to pH=7.5, filtered and deliquated, washed with 80% ethanol, filtered and deliquated, dried, and crushed to obtain CMC-Li. The performance indicators of the obtained carboxymethyl cellulose lithium are: DS=0.88, 1% aqueous solution viscosity 8000cP, purity 99.5%, Na≤1000ppm.

[0037] The present invention is further described in detail below with reference to Examples and Comparative Examples.

[0038] Example

[0039] Example 1

[0040] This embodiment discloses a method for preparing a modified lithium iron manganese phosphate positive electrode material, comprising the following steps:

[0041] (1) Primary coating: 0.40 kg of lithium carboxymethyl cellulose was dissolved in 5 kg of deionized water to obtain a lithium carboxymethyl cellulose aqueous solution. 6 kg of lithium iron manganese phosphate powder was put into the lithium carboxymethyl cellulose aqueous solution and dispersed evenly by ball milling. The primary coating material was obtained after drying at 120 °C for 1.5 h.

[0042] (2) Secondary coating: 0.05 kg of lithium iron phosphate powder and 0.10 kg of lithium carboxymethyl cellulose (weight ratio of 0.5:1) were dispersed in 5 kg of deionized water to obtain a mixture, the primary coating material obtained in step (1) was added to the mixture and evenly dispersed by ball milling, and the secondary coating material was obtained after drying at 140°C for 2 h;

[0043] (3) Sintering and compounding: 5.93 kg of (NH4)2HPO4, 5.99 kg of FeC2O4·2H2O and 2.01 kg of Li2CO3 were added to the secondary coating material obtained in step (2) in sequence and mixed evenly. The mixture was heated to 170°C for hydrothermal reaction for 8 h. The product was collected by centrifugation, washed alternately with deionized water and ethanol for 3 times, and dried at 100°C in vacuum for 2 h to obtain a precursor. The precursor was ground and heated to 320°C at a heating rate of 5°C / min under an argon atmosphere for pre-calcination for 2 h. The mixture was heated to 800°C at a heating rate of 10°C / min for calcination for 7 h to obtain a modified lithium iron manganese phosphate positive electrode material.

[0044] According to the content determination, in the modified lithium iron manganese phosphate positive electrode material obtained, the lithium carboxymethyl cellulose coated once forms the first buffer layer after sintering, the lithium iron manganese phosphate powder is wrapped by the first buffer layer as the lithium iron manganese phosphate core, the mixture of lithium iron phosphate and lithium carboxymethyl cellulose coated twice forms the second buffer layer after sintering, and (NH4)2HPO4, FeC2O4·2H2O and Li2CO3 form the lithium iron phosphate shell after hydrothermal reaction and sintering. The weight ratio of the lithium iron manganese phosphate core, the first buffer layer and the second buffer layer is 60:3:1. The lithium iron manganese phosphate core, the first buffer layer and the second buffer layer constitute the lithium iron manganese phosphate core material, and the weight ratio of the lithium iron manganese phosphate core material and the lithium iron phosphate shell is 64:36.

[0045] Example 2

[0046] This embodiment discloses a method for preparing a modified lithium iron manganese phosphate positive electrode material, comprising the following steps:

[0047] (1) Primary coating: 0.40 kg of lithium carboxymethyl cellulose was dissolved in 5 kg of deionized water to obtain a lithium carboxymethyl cellulose aqueous solution. 5.6 kg of lithium iron manganese phosphate powder was added to the lithium carboxymethyl cellulose aqueous solution and ball-milled to disperse the powder evenly. The primary coating material was obtained after drying at 120 °C for 1.5 h.

[0048] (2) Secondary coating: 0.05 kg of lithium iron phosphate powder and 0.10 kg of lithium carboxymethyl cellulose (weight ratio of 0.5:1) were dispersed in 5 kg of deionized water to obtain a mixture, the primary coating material obtained in step (1) was added to the mixture and evenly dispersed by ball milling, and the secondary coating material was obtained after drying at 140°C for 2 h;

[0049] (3) Sintering composite: 6.58 kg of (NH4)2HPO4, 6.65 kg of FeC2O4·2H2O and 2.23 kg of Li2CO3 were added to the secondary coating material obtained in step (2) in sequence and mixed, and the temperature was continued to be raised to 170°C for hydrothermal reaction for 8 h. The product was collected by centrifugation, washed alternately with deionized water and ethanol for 3 times, and vacuum dried at 100°C for 2 h to obtain a precursor. The precursor was then ground and heated to 320°C at a heating rate of 5°C / min under an argon atmosphere for pre-calcination for 2 h, and then heated to 800°C at a heating rate of 10°C / min for calcination for 7 h to obtain a modified lithium iron manganese phosphate positive electrode material.

[0050] According to the content measurement, the weight ratio of the lithium iron manganese phosphate core, the first buffer layer and the second buffer layer is 56:3:1. The lithium iron manganese phosphate core, the first buffer layer and the second buffer layer constitute the lithium iron manganese phosphate core material, and the weight ratio of the lithium iron manganese phosphate core material and the lithium iron phosphate shell is 60:40.

[0051] Example 3

[0052] This embodiment discloses a method for preparing a modified lithium iron manganese phosphate positive electrode material, comprising the following steps:

[0053] (1) Primary coating: 0.32 kg of lithium carboxymethyl cellulose was dissolved in 5 kg of deionized water to obtain a lithium carboxymethyl cellulose aqueous solution. 6.7 kg of lithium iron manganese phosphate powder was added to the lithium carboxymethyl cellulose aqueous solution and ball-milled to disperse the powder evenly. The primary coating material was obtained after drying at 120 °C for 1.5 h.

[0054] (2) Secondary coating: 0.05 kg of lithium iron phosphate powder and 0.10 kg of lithium carboxymethyl cellulose (weight ratio of 0.5:1) were dispersed in 5 kg of deionized water to obtain a mixture, the primary coating material obtained in step (1) was added to the mixture and evenly dispersed by ball milling, and the secondary coating material was obtained after drying at 140°C for 2 h;

[0055] (3) Sintering composite: 4.94 kg of (NH4)2HPO4, 4.99 kg of FeC2O4·2H2O and 1.67 kg of Li2CO3 were added to the secondary coating material obtained in step (2) in sequence and mixed. The mixture was heated to 170°C for hydrothermal reaction for 8 h. The product was collected by centrifugation, washed alternately with deionized water and ethanol for 3 times, and dried at 100°C in vacuum for 2 h to obtain a precursor. The precursor was ground and heated to 320°C at a heating rate of 5°C / min under argon atmosphere for pre-calcination for 2 h. The mixture was heated to 800°C at a heating rate of 10°C / min for calcination for 7 h to obtain a modified lithium iron manganese phosphate positive electrode material.

[0056] According to the content measurement, the weight ratio of the lithium iron manganese phosphate core, the first buffer layer and the second buffer layer is 67:2:1. The lithium iron manganese phosphate core, the first buffer layer and the second buffer layer constitute the lithium iron manganese phosphate core material, and the weight ratio of the lithium iron manganese phosphate core material and the lithium iron phosphate shell is 70:30.

[0057] Embodiment 4-5

[0058] In Example 4-5, based on the method of Example 1, the weight ratio of lithium iron phosphate to lithium carboxymethyl cellulose in the secondary coating of step (2) is adjusted. Among them, the weight ratio of lithium iron phosphate to lithium carboxymethyl cellulose in Example 4 is 0.3:1, and the weight ratio of lithium iron phosphate to lithium carboxymethyl cellulose in Example 5 is 0.6:1. In the modified lithium iron manganese phosphate positive electrode materials obtained in the two examples, the weight ratio of the lithium iron manganese phosphate core, the first buffer layer and the second buffer layer is 60:3:1. The lithium iron manganese phosphate core, the first buffer layer and the second buffer layer constitute the lithium iron manganese phosphate core material, and the weight ratio of the lithium iron manganese phosphate core material and the lithium iron phosphate shell is 64:36.

[0059] Examples 6-10

[0060] Examples 6-10 are based on the method of Example 1, with the process parameters adjusted. For specific adjustments, see Table 1 below.

[0061] Table 1 Process parameters of Example 1 and Examples 6-10

[0062]

[0063] Comparative Example

[0064] Comparative Example 1

[0065] This comparative example discloses a method for preparing a modified lithium iron manganese phosphate positive electrode material, comprising the following steps:

[0066] (1) Coating: 0.82 kg of lithium carboxymethyl cellulose was dissolved in 5 kg of deionized water to obtain a lithium carboxymethyl cellulose aqueous solution. 6 kg of lithium iron manganese phosphate powder was put into the lithium carboxymethyl cellulose aqueous solution and dispersed evenly by ball milling. The mixture was dried at 120 ° C for 1.5 h and then continued to be dried at 140 ° C for 2 h to obtain a coating material.

[0067] (2) Sintering composite: 5.93 kg of (NH4)2HPO4, 5.99 kg of FeC2O4·2H2O and 2.01 kg of Li2CO3 were added to the coating material obtained in step (1) in sequence and mixed evenly. The mixture was heated to 170°C for hydrothermal reaction for 8 h. The product was collected by centrifugation, washed alternately with deionized water and ethanol for 3 times, and dried at 100°C in vacuum for 2 h to obtain a precursor. The precursor was ground and heated to 320°C at a heating rate of 5°C / min under argon atmosphere for pre-calcination for 2 h. The mixture was heated to 800°C at a heating rate of 10°C / min for calcination for 7 h to obtain a modified lithium iron manganese phosphate positive electrode material.

[0068] According to the content determination, in the modified lithium iron manganese phosphate positive electrode material obtained, the coated lithium carboxymethyl cellulose forms a buffer layer after sintering, the lithium iron manganese phosphate powder is wrapped by the buffer layer as the lithium iron manganese phosphate core, and (NH4)2HPO4, FeC2O4·2H2O and Li2CO3 form the lithium iron phosphate shell after hydrothermal reaction and sintering. The weight ratio of the lithium iron manganese phosphate core to the buffer layer is 60:4. The lithium iron manganese phosphate core and the buffer layer constitute the lithium iron manganese phosphate core material, and the weight ratio of the lithium iron manganese phosphate core material to the lithium iron phosphate shell is 64:36.

[0069] Comparative Example 2

[0070] This comparative example discloses a method for preparing a modified lithium iron manganese phosphate positive electrode material, comprising the following steps:

[0071] (1) Preparation of lithium iron manganese phosphate core material

[0072] 0.06 kg of glucose was added to 6 kg of lithium iron manganese phosphate powder, and the mixture was evenly mixed by ball milling, and then the mixture was heated to 700 ° C at a heating rate of 5 ° C / min in an argon atmosphere for calcination for 8 hours, and then naturally cooled to obtain the lithium iron manganese phosphate core material;

[0073] (2) Mixing hexadecyltrimethylammonium bromide with water to obtain a dispersion solution with a mass concentration of 6%, mixing the lithium iron manganese phosphate core material with the dispersion solution according to a molar ratio of lithium iron manganese phosphate: hexadecyltrimethylammonium bromide = 1:0.2, and ultrasonically dispersing for 3 hours to obtain a spherical composite material of lithium iron manganese phosphate, then heating at 70°C with stirring, slowly adding cyclohexane, the molar ratio of hexadecyltrimethylammonium bromide to cyclohexane being 1:0.08, stirring for 0.8 hours after the addition is completed, to obtain a coating material;

[0074] (3) Add 5.93 kg of (NH4)2HPO4, 5.99 kg of FeC2O4·2H2O and 2.01 kg of Li2CO3 to the coating material obtained in step (2) in sequence and mix well. Continue to heat to 170°C for hydrothermal reaction for 8 h. Collect the product by centrifugation, wash it alternately with deionized water and ethanol for 3 times, and vacuum dry it at 100°C for 2 h to obtain a precursor. Grind the precursor, and then heat it to 320°C at a heating rate of 5°C / min in an argon atmosphere for pre-calcination for 2 h. Then heat it to 800°C at a heating rate of 10°C / min and calcine it for 7 h to obtain a modified lithium iron manganese phosphate positive electrode material.

[0075] Performance testing

[0076] The modified lithium iron manganese phosphate positive electrode material obtained in the above examples 1-10 and comparative examples 1-2 was uniformly mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 90:5:5 in N-methylpyrrolidone, and then coated on aluminum foil and placed in a vacuum drying oven for drying. After drying, the battery was assembled in an argon glove box and pressed into a positive electrode sheet by a sheet press. The negative electrode was a metal lithium sheet, and the electrolyte was 1M (volume ratio 1:1), polypropylene porous membrane as separator. The electrochemical performance was tested, and the test results are shown in Table 2 below.

[0077] Table 2 Test results of Examples 1-10 and Comparative Examples 1-2

[0078]

[0079] Referring to Table 2, comparing the embodiments of the present invention with the comparative examples, the embodiments of the present invention have more excellent conductivity, and also have excellent first charge, first efficiency and discharge capacity. Therefore, it can be concluded that the present invention designs a core-shell structure with lithium iron manganese phosphate as the core and lithium iron phosphate as the shell, wherein the first buffer layer and the second buffer layer serve as the intermediate skeleton, which can not only effectively inhibit the dissolution of manganese, but also increase the specific surface area of ​​the material to shorten the lithium ion transmission distance, facilitate faster escape and embedding of lithium ions in the lithium iron manganese phosphate core, and further improve the electrical properties of the positive electrode material.

[0080] By comparing the test results of Examples 1-3, it can be obtained that when the weight ratio of the lithium iron phosphate manganese core material and the lithium iron phosphate shell of the present invention is 60-70:40-30, and the weight ratio of the lithium iron phosphate manganese core body, the first buffer layer and the second buffer layer in the lithium iron phosphate manganese core material is 56-67:2-3:1, the modified lithium iron phosphate manganese positive electrode material obtained has a more excellent conductivity, and its corresponding first charge amount, first charge efficiency and discharge capacity at 0.1C, 1C and 3C are higher, so it is preferred as the present invention. Among them, it is further preferred that the weight ratio of the lithium iron phosphate manganese core material and the lithium iron phosphate shell is 64:36, and the weight ratio of the lithium iron phosphate manganese core body, the first buffer layer and the second buffer layer in the lithium iron phosphate manganese core material is 60:3:1.

[0081] Comparing the test results of Example 1 with those of Examples 4-5, it can be found that when the weight ratio of lithium iron phosphate to lithium carboxymethyl cellulose in the second buffer layer of the present invention is 0.3:1, the reduction in the content of lithium iron phosphate will not only significantly reduce the conductivity of the material, but also affect the first charge and discharge capacity to a certain extent; when the weight ratio of lithium iron phosphate to lithium carboxymethyl cellulose rises to 0.6:1, the improvement effect of lithium iron phosphate on conductivity decreases, and the corresponding first charge and discharge capacity also show a slightly downward trend. Therefore, from a comprehensive consideration, the present invention preferably uses a weight ratio of 0.3-0.6:1, and it is not appropriate to adjust its dosage at will.

[0082] By comparing the test results of Example 1 with those of Examples 6-10, it can be obtained that, when preparing the modified lithium iron manganese phosphate positive electrode material, the present invention adopts a primary coating to perform preliminary shaping first, and then uses a secondary coating to ensure the basic structure of the lithium iron manganese phosphate core, and finally sintering and composite forming in one time, which can reduce the calcination steps of preparing the lithium iron manganese phosphate core separately; in addition, the lithium iron phosphate shell in the present invention is formed by first adding raw materials and then sintering, which helps to improve the composite effect of the lithium iron phosphate shell and the second buffer layer, reduce the interface resistance, and further improve the conductivity of the positive electrode material.

[0083] Among them, the first buffer layer and the second buffer layer of the present invention can firmly bond the lithium iron manganese phosphate core to the lithium iron phosphate shell before sintering, and water vapor, carbon monoxide, carbon dioxide, etc. will also be generated during the sintering process, which can not only cause pores in the buffer layer itself, but also form more pores on the lithium iron phosphate shell coated on the outer layer, thereby forming a conductive network channel inside the positive electrode material, increasing the specific surface area of ​​the material to shorten the lithium ion transmission distance, and facilitating the lithium ions in the lithium iron manganese phosphate core to be able to escape and embed faster.

[0084] In order to effectively control the exhaust of gas, it is necessary to strictly control the drying temperature and time during the first coating, the drying temperature and time during the second coating, the hydrothermal temperature and time during the sintering and compounding, the pre-sintering temperature and time, and the calcining temperature and time. Specifically, "drying at 100-120℃ for 1-2h in the first coating step, drying at 130-150℃ for 1-2h in the second coating step, hydrothermal reaction at 160-180℃ for 6-8h in the sintering and compounding step, pre-sintering at 300-350℃ for 2-3h, and calcining at 750-800℃ for 6-8h".

[0085] Application Examples

[0086] In this application example, the modified lithium iron manganese phosphate positive electrode material prepared in any one of Examples 1-10 can be used to prepare a lithium-ion battery positive electrode, wherein the lithium-ion battery positive electrode prepared corresponding to the modified lithium iron manganese phosphate positive electrode material of Example 1 is further preferred. The positive electrode not only has a high conductivity, but also has excellent first charge and discharge capacity, and has broad application prospects.

[0087] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A modified lithium iron manganese phosphate positive electrode material, characterized in that: It comprises a lithium iron manganese phosphate core material and a lithium iron phosphate shell coated outside the lithium iron manganese phosphate core material; the lithium iron manganese phosphate core material comprises a lithium iron manganese phosphate core body, a first buffer layer coated outside the lithium iron manganese phosphate core body, and a second buffer layer coated outside the first buffer layer; the first buffer layer is mainly sintered from lithium carboxymethyl cellulose, and the second buffer layer is mainly sintered from a mixture of lithium iron phosphate and lithium carboxymethyl cellulose; The weight ratio of the lithium iron phosphate manganese core material to the lithium iron phosphate shell is 60-70:40-30, the weight ratio of the lithium iron phosphate manganese core body, the first buffer layer and the second buffer layer in the lithium iron phosphate manganese core material is 56-67:2-3:1, and the weight ratio of the lithium iron phosphate and the lithium carboxymethyl cellulose is 0.3-0.6:

1.

2. The modified lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The weight ratio of the lithium iron manganese phosphate core, the first buffer layer and the second buffer layer in the lithium iron manganese phosphate core material is 60:3:

1.

3. The method for preparing the modified lithium iron manganese phosphate positive electrode material according to claim 1 or 2, characterized in that: The following steps are involved: Primary coating: Take an appropriate amount of lithium iron manganese phosphate powder and put it into an aqueous solution of lithium carboxymethyl cellulose for uniform dispersion by ball milling, and harvest the primary coating material after drying; Secondary coating: taking a set amount of lithium iron phosphate and lithium carboxymethyl cellulose and dispersing them in water to obtain a mixture, adding the primary coating material into the mixture and ball milling to disperse it evenly, and harvesting the secondary coating material after drying; Sintering composite: adding a phosphorus source, an iron source and a lithium source to the secondary coating material and mixing them evenly, firstly performing a hydrothermal reaction to obtain a precursor, and then performing a sintering treatment on the precursor to obtain the modified lithium iron manganese phosphate positive electrode material.

4. The preparation method according to claim 3, characterized in that: In the first coating step, the drying treatment condition is drying at a temperature of 100-120° C. for 1-2 hours; in the second coating step, the drying treatment condition is drying at a temperature of 130-150° C. for 1-2 hours.

5. The preparation method according to claim 3, characterized in that: In the sintering and compounding step, the hydrothermal reaction is carried out at a temperature of 160-180° C. for 6-8 hours.

6. The preparation method according to claim 3, characterized in that: In the sintering and compounding step, the sintering treatment includes pre-sintering and calcining, the pre-sintering is performed at a temperature of 300-350° C. for 2-3 hours, and the calcining is performed at a temperature of 750-800° C. for 6-8 hours.

7. Use of the modified lithium iron manganese phosphate positive electrode material according to claim 1 or 2 in preparing a positive electrode for a lithium ion battery.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate positive electrode material and preparation method thereof

    CN116873892A

  • Phosphate positive electrode material, preparation method and lithium battery application

    CN116470021A

  • Lithium ion battery material, battery and manufacturing method thereof

    CN116565179A